Fatigue Life Evaluation of Reducer Box of Beam Pumping Unit based on Rain Flow Method - Shang Huichao; Yang Shufeng (Jixie chuandong)
The light weight design of the reducer is one of the most important research topics in the field of mechanical transmission,the box is a very important part of the reducer. Because of its design method,few scholars have studied the stiffness,structural strength,fatigue reliability and the overall dynamics of gear. An example of the reducer box of a beam pumping unit is taken as an example,the curve of material is fitted,the stress-strain of the gearbox is analyzed,load spectrum of gear and crank in box is calculated,the fatigue life of the decelerated chassis is evaluated by the rain flow method in n Codes software. The problem of the fatigue life analysis method of the box is studied,which lays the foundation for the light weight design of the rear reducer box.